Genomic instability detected from the saliva of Head and Neck Squamous Cell Carcinoma patients: Association with clinical implications. (May 2022) - Boora, Geeta S.; Chauhan, Anshika; Kaur, Rajandeep; Kaur, Harmanjot; Chandel, Jitender; Bhat, Shabir A.; Ghoshal, Sushmita; Pal, Arnab
Abstract: Objectives: Genomic instability in cancers is often associated with poor disease outcomes. In Head and Neck Squamous Cell Carcinoma (HNSCC), saliva being the contact fluid contains cancers cells shed from the primary tumour. This study detected genomic instability from cancer cells shed in saliva and correlated the same with clinical implications. Design: Genomic instability in HNSCC patients (n = 81) was analysed and compared with control subjects (n = 30). Alu sequences were amplified from the DNA of the cells shed in saliva and from the blood (Germline DNA) using Alu -PCR. Band variations between amplified products of salivary cells' DNA and germline DNA were compared. ' Instability Score' was calculated by counting the band variation(s). The ' Instability Score' was further used as a measure of genomic instability. Results: Higher instability was detected in patients as compared to the controls (p < 0.0001). After treatment, there was a significant decrease (p < 0.0001) in the Instability score and patients with higher instability scores responded better to radiotherapy. The patient group consuming both tobacco and alcohol had a higher instability score in comparison to the tobacco group (p = 0.0056). Also, Instability scores are inversely correlated with nodal metastasis (p = 0.0075). A high Instability score before treatment resulted in a better prognosis in HNSCC patients (HR: 1.8, 95%CI: 1.024–3.164, p = 0.0306). Conclusion: Our data suggest that genomic instability estimated from the tumour cells shed in the saliva of HNSCC patients by amplifying Alu sequence ( Alu -PCR) is associated with radiotherapy response. Highlights: Genomic instability is an important aspect of carcinogenesis. Saliva is a contact fluid, therefore is the fluid of choice for the identification of various potential biomarkers. Genomic instability was detected by using a non-invasive and cost-effective technique i.e. Alu-PCR. Genomic instability was found to be reduced post-treatment. Higher genomic instability prior to treatment correlates with better overall survival.